Morphophysiology of the male reproductive accessory glands of the bat Pteronotus gymnonotus (Mormoopidae: Chiroptera) - Pimentel, Pollyana B.; Santigo, Cornélio S.; Ferraz, Juliana F.; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastião R. [UNESP]; Souza, Carolina C.; Beguelini, Mateus R. (Elsevier, 2023)
Mormoopidae is an exclusive Neotropical family of bats, distributed from southern Mexico to northeastern Brazil. Possibly due to its endemic distribution and very low occurrence (rarity), descriptions of their reproductive accessory glands (RAGs) are still lacking. Thus, this study aims to characterize the male RAGs of Pteronotus gymnonotus (Mormoopidae: Chiroptera). Results demonstrate that the RAGs of P. gymnonotus is composed of a prostatic complex, comprising two regions (ventral and dorsal prostates); urethral (Littre) glands, a pair of bulbourethral and ampullary glands, with the absence of seminal vesicles. The ventral prostate has an atypical epithelium, due to its holocrine secretion; which contains numerous PAS-positive globular vesicles. The dorsal prostate has a cubic-to-columnar pseudostratified epithelium, containing fluid PAS-negative secretion. The ampullary glands present cubic-to-columnar pseudostratified epithelium, with secretion varying from granular and PAS-negative to fluid and PAS-positive. Urethral glands are dispersed in the submucosa of the urethra, while the bulbourethral glands are located in the penile root. Both glands have cubic-to-columnar pseudostratified epithelium with PAS-positive globular secretion. In conclusion, we propose that the RAGs of P. gymnonotus possibly evolved from a common emballonurid ancestor, shared with the families Phyllostomidae and Noctilionidae, but with the development of an exclusive apomorphy, the ampullary glands.
Keywords: Ampullary gland; Bulbourethral gland; Prostate, Reproduction